Anti-Angiogenesis Drug Discovery and Development: Volume 5 - Atta-ur-Rahman; Iqbal Choudhary, Muhammad (Bentham Science Publishers, 2020)
The inhibition of angiogenesis is an effective mechanism of slowing down tumor growth and malignancies. The process of induction or pro-angiogenesis is highly desirable for the treatment of cardiovascular diseases, and wound healing disorders. Efforts to understand the molecular basis, both for inhibition and induction, have yielded fascinating results.Anti-angiogenesis Drug Discovery and Development provides an excellent compilation of well-written reviews on various aspects of the anti-angiogenesis process. These reviews have been contributed by leading practitioners in drug discovery science and highlight the major developments in this exciting field in the last two decades. The feast of these reader-friendly reviews on topics of great scientific importance – many of which are considered significant medical breakthroughs, makes this series excellent reading both for the novice as well as for expert medicinal chemists and clinicians.The fifth volume brings together reviews on the following topics:- Targeted therapy for tumor vasculature- Anti-angiogenic therapy for breast and prostate cancers (including information updates on clinical trials)- Microbe-based and other novel antiangiogenesis therapies such as chromene-based agents